Analysis of Gas Turbine Performance based on Variation of Operating Load at PLTGU Panaran 1 Unit 1 PT.Mitra Energi Batam - Purba, Jhon Hericson; Syafei Gozali, Muhammad; Fernando Sitohang, Ferri; Febriansyah Juwito, Arif; Jefiza, Adlian (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Gas and steam power generation units often experience changes in load according to the requested electricity needs. Changes in generator workload will also affect the efficiency of the generator. The different efficiency in each workload will have an effect on the amount of heat rate production produced when compared. By calculating the efficiency at each load, it will be useful to find out the workload with the best performance. From the results of the enthalpy calculation process based on the temperature of each gas turbine process, in this study the gas turbine performance is calculated, and then it compares the turbine performance with variations in operating load. The turbine performance that will be calculated includes compressor power, turbine power, net power, thermal efficiency, compressor efficiency, combustion chamber efficiency, turbine efficiency, heat input, and heat rate. The results of the calculation of the highest average thermal efficiency at 27 MW load were 35.18%; the average compressor efficiency experienced the highest increase at 25 MW load of 83.24%, followed by an average increase in combustion chamber efficiency and an average decrease in turbine efficiency at each increase in load, as well as experiencing the lowest decrease in heat rate at 27 MW load conditions of 2,842 kJ/kWh